Crimean‐Congo haemorrhagic fever‐induced liver injury: A systematic review and meta‐analysis. Issue 11 (12th September 2021) - Rathore, Sawai Singh; Manju, Ade Harrison; Wen, Qingqing; Sondhi, Manush; Pydi, Reshma; Haddad, Iskander; Hasan, Jamal; Ali, Muhammad Adnan; Tousif, Sohaib; Singh, Romil; Muhammed, Abdul‐Azeez; Ahmed, Noman Khurshid; et al.
Abstract: Background: Crimean‐Congo haemorrhagic fever (CCHF) is a fatal acute tick‐borne viral infection and substantial emerging global public health threat. This illness has a high case fatality rate of up to 40%. The liver is one of the important target organs of the CCHF virus. Objective: The aim of this meta‐analysis to evaluate the correlation between CCHF and liver injury and draw more generalised inferences about the abnormal serum markers of liver injury such as alanine aminotransferase (ALT), aspartate aminotransferase (AST) in CCHF patients. Methods: A literature search was accomplished for published eligible articles with MEDLINE/PubMed and Embase databases. All eligible observational studies and case series were included from around the world. The inclusion criteria were articles describing liver injury biomarkers amongst patients diagnosed with CCHF. Results: Data from 18 studies, consisting of 1238 patients with CCHF were included in this meta‐analysis. Overall pooled incidence of at least one raised liver injury biomarker was 77.95% (95% CI, I 2 = 88.50%, P < .0001). Similarly, pooled incidence of elevated AST and ALT was 85.92% (95% CI, I 2 = 85.27%, P < .0001) and 64.30% (95% CI, I 2 = 88.32%, P < .0001), respectively. Both Egger and Begg‐Mazumdar's tests detected no apparent publication bias in all three meta‐analyses ( P > .05). Conclusion: Our study shows that CCHF has a very detrimental effect on liver function. Abnormal liver function may lead to poor prognosis and increased morbidity and mortality in CCHF patients. Hence, Physicians must recognise and continuously monitor these biomarkers, since these markers may aid in early stratification of prognosis and the prevention of severe outcomes in infection with such a high case fatality rate.